Institutional Redesign Proposals for the Preparation of Criminal Policy by the Government. The Focus on Ex Ante Evaluations - Becerra-Muñoz, José (My University, 2016)
As many other countries, Spain is also experiencing a punitive turn in Criminal Justice Policy in the last 15 years, which is taking social narratives about crime and disorder as well as actual punishment to a parallel dimension that is quite often away from reality. While some strategies try to fight back from values and ideology or empirical studies to prove what works as well as the real effects of certain policies, my approach uses very different tools to tackle the issue: First, I´ll defend the suitability of Evaluation knowledge, from a Public Policy Analysis perspective, for the improvement of Criminal Justice Policy. Such perspective conceives Evaluation as much more than just a research tool and provides, in my opinion, a holistic approach that needs to be better connected with Spanish Criminal Justice Policy making in order to have a greater impact on it. Second, to ease such connection, I´ll propose a set of adjustments in the structure and tasks of institutions involved in Criminal Justice Policy creation. It is my view that for Evaluation to be considered a relevant tool in Spanish Criminal Justice Policy there should be some institutional changes I will try to explain in detail.
Keywords: Criminología; Derecho penal; Criminal policy making; Criminal policy evaluation; Institutional approach; Government